Clinical isolates of Candida auris with enhanced adherence and biofilm formation due to genomic amplification of ALS4. - Jian Bing; Zhangyue Guan; Tianhong Zheng; Zhijie Zhang; Shuru Fan; Craig L Ennis; Clarissa J Nobile; Guanghua Huang (PLoS Pathogens)
Candida auris is an emerging multidrug-resistant fungal pathogen and a new global threat to human health. A unique morphological feature of this fungus is its multicellular aggregating phenotype, which has been thought to be associated with defects in cell division. In this study, we report a new aggregating form of two clinical C. auris isolates with increased biofilm forming capacity due to enhanced adherence of adjacent cells and surfaces. Unlike the previously reported aggregating morphology, this new aggregating multicellular form of C. auris can become unicellular after treatment with proteinase K or trypsin. Genomic analysis demonstrated that amplification of the subtelomeric adhesin gene ALS4 is the reason behind the strain's enhanced adherence and biofilm forming capacities. Many clinical isolates of C. auris have variable copy numbers of ALS4, suggesting that this subtelomeric region exhibits instability. Global transcriptional profiling and quantitative real-time PCR assays indicated that genomic amplification of ALS4 results in a dramatic increase in overall levels of transcription. Compared to the previously characterized nonaggregative/yeast-form and aggregative-form strains of C. auris, this new Als4-mediated aggregative-form strain of C. auris displays several unique characteristics in terms of its biofilm formation, surface colonization, and virulence.